2021
DOI: 10.31557/apjcp.2021.22.1.233
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Bile Microbiome Identifies District Microbial Population between Choledocholithiasis and Cholangiocarcinoma Patients

Abstract: Objective: Choledocholithiasis (CDL), a potential risk for cholangiocarcinoma (CCA) development, is often a consequence of bacterial infection. Thus, the microbial population that contributes to CDL might also be involved in CCA development. We compared the microbiome in bile fluid of CDL patients and CCA patients. Methods: Bile samples were collected from CDL (n = 30) and CCA (n =30) patients. Microbial profiling was performed individually by the sequencing of V3-V4 regions of the 16S rRNA gene. Results: Ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…[34][35][36] Previous studies by Chai et al have explored the microbial characteristics within ICC, confirming the potential role of microbiota in cancer treatment. [6] In this study, we focused on the potential pro-cancerous effects of E. coli on the bile microenvironment. In line with previous studies, we confirmed that E. coli was the predominant bacterium in the bile of patients with ICC and hepatolithiasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36] Previous studies by Chai et al have explored the microbial characteristics within ICC, confirming the potential role of microbiota in cancer treatment. [6] In this study, we focused on the potential pro-cancerous effects of E. coli on the bile microenvironment. In line with previous studies, we confirmed that E. coli was the predominant bacterium in the bile of patients with ICC and hepatolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] While hepatolithiasis was once considered the primary cause of ICC, recent studies suggest that bacteria play a significant role in the formation of hepatolithiasis and the progression of ICC. [ 5 ] Bacteria facilitate the occurrence of hepatolithiasis by interacting with host bile tissue, [ 6 ] which leads to hepatolithiasis‐induced cholestasis, bacterial proliferation, and inflammatory responses. These events promote ICC progression.…”
Section: Introductionmentioning
confidence: 99%
“…A 71-year-old male German patient presented to the emergency department with acute cholangitis caused by a perihilar cholangiocarcinoma, also known as “Klatskin tumor” [ 26 , 27 ], with hepatic and lymphogenic metastases. Comorbidities included chronic kidney insufficiency (KDIGO G2), type 2 diabetes mellitus and paroxysmal atrial fibrillation.…”
Section: Methodsmentioning
confidence: 99%
“…Until recently, bile was considered a sterile fluid, but more recent reports show that a unique microbial ecosystem exists in subjects with and without hepatobiliary disorders [ 120 ]. Not only are cholestatic liver diseases associated with bile microbial alterations, but the bile microbiome also seems to vary by the etiology of cholestasis [ 121 , 122 ]. A pilot study from Finland by Färkkilä and colleagues revealed minor to no microbiome alterations in PSC patients compared to healthy controls [ 123 ].…”
Section: Evidence From Human Case–control Microbiome Studiesmentioning
confidence: 99%